El ciberacoso como forma de violencia de género y la vulneración a los derechos a la integridad personal, al honor y al buen nombre y a la no discriminación - Chicaiza Morocho, Cynthya Anabella (2025)
This study addresses cyberbullying as a form of gender-based violence within the Ecuadorian legal context by analyzing its impact in the violation of rights to personal integrity, honor and good name, and no discrimination. The main objective was to evaluate the absence of legal classification of cyberbullying in the Ecuadorian regulation and to propose solutions to guarantee fundamental rights of the victims. The methodology used included a mixed approach, in other words, a combination of the quantitative and qualitative methods. Surveys were conducted with a sample of university students as well as interviews with legal experts. The analysis of the data showed that a significant part of the participants in the survey were victims of cyberbullying. Additionally, it was identified that most of the participants considered that the current Ecuadorian legislation is insufficient to address the problem; likewise, it highlighted the need of a legal reform that addresses all types of cyberbullying. In conclusion, the lack of a specific legal classification for cyberbullying leaves victims in a state of defenselessness. It is important to strengthen the legal frame and create mechanisms of accessible reports for the victims.